The case of monkeypox in Serbia in 2022 - case report and literature review - Pocevski, Božidar P; Pocevski, Marija; Pocevski, Predrag; Gvozdenović, Eleonora М (General Practice, 2025)
Introduction. The Monkeypox virus (MPXV, also known as Mpox) is part of the Orthopoxvirus family, which includes some of the largest and most complex viruses studied in virology.Case report. A 28-year-old male patient was examined in a general practitioner’s office. During the examination, skin lesions were found, including a panaritium on the smallphalanx of his left hand and two maculopapular lesions at the dorsal root of the penis. The physical examination indicated a viral infection, prompting the ordering of viral serology tests. The patient was advised to use symptomatic therapy, includinganalgesics, antipyretics, anti-inflammatory medications, and vitamins. For the skin lesions, he was instructed to apply 70% alcohol, 3% hydrogen peroxide, and 10% povidone-iodine, as well as antiviral creams. The panaritium was drained, and local antibiotics were used. General symptoms resolved five days after starting therapy, and the skin lesions fully epithelized within 22 days from the onset.Conclusion. General practitioners should continuously improve their skills to recognize less common pathologies, particularly those that are newly emerging. Satisfaction comesfrom the ability to identify diseases and alleviate symptoms through dedicated knowledge, effort, and commitment. This is achieved by familiarizing oneself with the pathophysiology and clinical presentation of the relevant conditions.
Keywords: monkeypox; mpox; epidemic; contagoius diseases; infectious diseases